High platelet reactivity is a predictor of left ventricular remodelling in patients with acute myocardial infarction. (31st July 2022) - Tsuji, Masahiro; Kawai, Yusuke; Miyoshi, Toru; Saito, Eisuke; Kawamura, Kohei; Ono, Tamaki; Tokioka, Koji; Ohe, Tohru; Nakamura, Kazufumi; Ito, Hiroshi
Abstract: Aims: Acute myocardial infarction (AMI) is associated with left ventricular remodelling (LVR), which leads to progressive heart failure. Platelets play a pivotal role in promoting systemic and cardiac inflammatory responses during the complex process of myocardial wound healing or repair following AMI. This study aimed to investigate the impact of platelet reactivity immediately after primary percutaneous coronary intervention (PCI) on LVR in AMI patients with ST‐segment (STEMI) and non‐ST‐segment elevation (NSTEMI). Methods and results: This prospective, single‐centre, observational study included 182 patients with AMI who underwent primary PCI (107 patient with STEMI and 75 patients with NSTEMI). Patients were administered a loading dose of aspirin plus prasugrel before the procedure, and platelet reactivity was assessed using the VerifyNow P2Y12 assay immediately after PCI. Echocardiography was performed before discharge and during the chronic phase (8 ± 3 months after discharge). LVR was defined as a relative ≥20% increase in left ventricular end‐diastolic volume index (LVEDVI). LVR in chronic phase was found in 34 patients (18.7%) whose platelet reactivity was significantly higher than those without LVR (259.6 ± 61.5 and 213.1 ± 74.8 P2Y12 reaction units [PRU]; P = 0.001). The occurrence of LVR did not differ between patients with STEMI and patients with NSTEMI (21.5% and 14.7%; P = 0.33). The optimal cut‐off value of platelet reactivity for discriminating LVR was ≥245 PRU. LVEDVI significantly decreased at chronic phase in patients without high platelet reactivity (<245 PRU) (from 49.2 ± 13.5 to 45.4 ± 15.8 mL/m 2 ; P = 0.02), but not in patients with high platelet reactivity (≥d245 PRU) ( P = 0.06). Multivariate logistic analysis showed that high platelet reactivity was an independent predictor of LVR after adjusting for LVEDVI before discharge (odds ratio, 4.13; 95% confidence interval, 1.85–9.79). Conclusions: High platelet reactivity measured immediately after PCI was a predictor of LVR in patients with AMI during the chronic phase. The role of antiplatelet therapy on inflammation in the myocardium is a promising area for further research.